Subject of Technology or Feminization of Technology? Critical Studies of Women’s Roles and Control in Science and Technology - Asriani, Desintha D. (Yayasan Jurnal Perempuan, 2016)
This article’s main purpose is to offer a critical perspective on the increased intensity of encouraging women’s role in science and technology. It is not to be denied that the effort to reconcile women with skills-based technology can be a strategic way to free women from science segregation. Nevertheless, technology, especially in an industrial society, is also a commodity, and it is often utilized for the flow of profits in which women tend to be mere objects. This paper emphasizes that the effort to popularize women’s role in the field of science and technology should be followed by education for women about the importance of being a fully selfaware subject. Thus, women’s contributions to the evolution of technology should always be understood as a process of women’s liberation rather than as a trap that ensnares them in exploitative practices.